Cultural-historical resources as initiators of tourism development in Sremski Karlovci - Sančanin, Branislav; Perić, Goran; Stojiljković, Marija (Hotel and Tourism Management, 2019)
Cultural heritage is an authentic and unrepeatable resource. Cultural, economic, political, and ecological facts evaluate its observations, both qualitatively and quantitatively. Therefore, we won’t exaggerate if we say that cultural heritage should have the status of a strategic resource. In this way, both cultural revitalization and general sustainable development are based on it. The scope and dynamics of conducting complex activities, which unite the restoration, conservation, renovation, revitalization, sanitation, and presentation of protected cultural heritage, condition the preservation and promotion of categorized and immovable cultural heritage. The creation of cultural-historical heritage of Sremski Karlovci and its gradual and systematic tourist valorization are the basis for deepening our understanding of its potential. This potential is based on the effective politics of heritage management. It can become an experience and provide pointers for sustainable development. Establishing a correlation between the most important attractions and multipliers supports the necessary move from the multidisciplinary approach to tourism development to an interdisciplinary one. This approach should help one shape and achieve the goals of the development of culture and tourism by relying on cross-sector and interdepartmental connections, and continued cooperation.